AN INVESTIGATION OF CHINESE CONSUMERS’ USER EXPERIENCE ON APPs FOR DIGITAL HERITAGE COLLECTIONS - Ziwei, Lyu; Norfarizah Mohd Bakhir; Shuangping, Ouyang (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
The digital cultural and creative industry is developing very rapidly, however, the research on its consumer user experience has not received much attention. This study aims to investigate Chinese consumers’ user experience with digital heritage collection apps and examines whether they differ by gender, age, and education level. This study adopts a random sampling survey and collects 1587 questionnaire data using the scale adapted by the researcher. The collected data were analysed using SPSS 26. The results found that the overall user experience score of consumers is not high (3.52), the sensory experience is significantly higher than other experience, and the average value of innovation experience is the lowest. The difference analysis data presented that gender has no significant difference in consumers’ user experience, but age and education level have significant difference. Additionally, the researcher also proposed three strategies from the perspective of product design to improve consumer user experience.